THE EFFECT OF TPS STRATEGY ON STUDENTS’ LISTENING SKILLS USING POLAROID SONG AT PERGURUAN BUDDHIS BODHICITTA JUNIOR HIGH SCHOOL - HONGKO hongko (elt, 2020)
The effect of TPS Strategy particularly in listening is very important in the study of English language because listening skills are often considered critical in building communication. It provides a new technique which can be applied in listening. This research, however, is to find out whether TPS Strategy significantly affects students’ listening skills at PERGURUAN BUDDHIS BODHICITTA JUNIOR HIGH SCHOOL. The result shows that both pre-test and post-test were accumulated in to two different class groups namely, experimental (using TPS Strategy) and controlled group (not using TPS Strategy). The experimental group in pre-test has resulted 58.5 in average while the post-test has resulted 75.5 in average. On the other hand, the controlled group in the pre-test has resulted 52.8 in average whereas the post-test has resulted 62.2 in average. From the result, it was clear that the use of TPS Strategy (experimental group) gave significant effect on students listening skills. Key Words: Effect, TPS Strategy, Listening Skills